Strategies used to combat stress among dental college students: an Indian outlook - Sekhon, Tegbir Singh; Grewal, Simran; Gambhir, Ramandeep Singh; Dhaliwal, Jagjit Singh (International Journal Of Community Medicine And Public Health, 2017)
Background: Coping strategies when used effectively buffer the unwanted impacts of stressful situation on physical, emotional and mental wellbeing. The purpose of the present study was to address various stress coping strategies utilized by Indian dental school students. Methods: A questionnaire based cross-sectional study was conducted among third and fourth year students of a dental school. Modified version of brief COPE Scale was used to assess various coping methods used by the students. A four point Likert scale was used to record the responses from the subjects. A total of 174 subjects participated in the study. Statistical analysis was conducted using chi-square test and multiple regression analysis. Results: Of the participants, 39% (68) were males and 61% (106) were females. TV/music/internet/hobby was used by 98% of students to combat stress. Being optimistic in spite of what has happened was indicated by 99% of students as a measure for relieving. Males, older students and students who chose dentistry as their first career preference utilized more coping strategies (p<0.05). Conclusion: Majority of the students adopted positive coping strategies like planning, active coping, positive reframing, use of TV/music/internet/hobby, emotional and instrumental support etc. There is an urgent need for structured stress intervention programs in a country like India.